Aluminum and Inorganic Natural Pigment Colored Composites by Powder Metallurgy Forming - Miguel Angel Martínez; Juana Abenojar (Metals)
Aluminum powder, along with other powders such as steel or stainless steel, is extensively used in powder metallurgy (PM) to produce complex samples with irregular geometric shapes. PM enables the incorporation of fillers to modify the physical, mechanical, or wear properties of aluminum without melting, thereby preventing phase segregation. The novelty of this work lies in the use of inorganic natural pigments (INPs). The primary goal of this study is to produce colored aluminum samples via PM without compromising their mechanical properties. INPs are first characterized to select those with the highest heat resistance. The composites are fabricated with different pigments (10 wt%), formed through uniaxial compaction at 500 MPa, and sintered in a nitrogen atmosphere at 610 °C for 30 min. Density, color, bending strength, and wear are evaluated to identify the most suitable pigment for gas kitchen burners. Mars red, Cobalt blue, and Chrome green pigments provide the best coloration. Dimensional variation is generally less than 1%. The pigments increase the material’s brittleness by 41% to 77%, resulting in a bending modulus increase of up to 160% and deformation reduction of up to 70%. In some cases, intermetallic compounds improve bending strength, as in Al–Chrome green, by 30%. Al–Chrome green exhibits wear resistance comparable to aluminum, with a 40% lower friction coefficient. X-ray diffraction and SEM-EDX confirm AlCr and AlCo intermetallic particles. Thermal stability is verified after 160 heating and cooling cycles without significant material degradation.